2022
DOI: 10.1093/jpp/rgab151
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil protects heart from myocardial ischaemia/reperfusion (I/R) injury via miR-206-3p/TLR4/NF-κB signalling axis

Abstract: Objectives Myocardial I/R injury is one of the most serious complications after reperfusion therapy in patients with myocardial infarction. Remifentanil has been found to protect the heart against I/R injury. However, its underlying mechanism remains uncertain in myocardial I/R injury. Methods The myocardial I/R injury rat model was established by 30 min of ischaemia followed by 24 h of reperfusion. The animal model was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Yang et al also showed that miR-206 contributed to cardiomyocyte hypertrophy and survival by regulating YAP [ 25 ]. Moreover, Zhang et al's also highlighted that a decrease in miR-206 could impair cardiac function and promote oxidative stress by removing the inhibitory role of TLR4[ 26 ]. These data implied that miR-206 was most likely a heart-protective factor.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al also showed that miR-206 contributed to cardiomyocyte hypertrophy and survival by regulating YAP [ 25 ]. Moreover, Zhang et al's also highlighted that a decrease in miR-206 could impair cardiac function and promote oxidative stress by removing the inhibitory role of TLR4[ 26 ]. These data implied that miR-206 was most likely a heart-protective factor.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zhang et al found that remifentanil protected myocardial I/R injury by modulating the TLR4/NF-κB signaling pathway. Simultaneously, they found that the defense mechanism involved miRNA-206-3p, which plays a significant role in downregulating the expression of TLR4 45 . Therefore, in the current study, we sought to ascertain the potential protective function of miRNA-206-3p against LPS-induced ALI www.nature.com/scientificreports/ by specifically targeting TLR4.…”
Section: Discussionmentioning
confidence: 94%
“…Dong et al reported a protective role for miRNA-206 against myocardial inflammatory injuries induced by targeting the USP33, which may be a reliable therapeutic target 43 . Meanwhile, Zhou et al found that the effects of miRNA-206-3p on connexin, ultimately improving lung permeability in sepsis-induced ALI 44 .Some widely used medications, including remifentanil, protect the heart against the damage caused by myocardial ischemia/ reperfusion (I/R) by modulating the miRNA-206-3p 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The NF- κ B family plays a critical role in numerous biological processes, including apoptosis and inflammatory responses ( Karin & Greten, 2005 ; Courtois & Gilmore, 2006 ). When cardiomyocytes are stimulated by various chemical and mechanical signals, such as I/R, NF- κ B is activated ( Xiong et al, 2021 ; Zhang et al, 2022 ). Therefore, we investigated the effect of TRIM38 on NF- κ B signalling.…”
Section: Discussionmentioning
confidence: 99%